Implementation of Inquiry and Group Methods Investigation in PJOK Towards Student’s Participation and Critical Thinking - Eka Cahyadi; Agus Hariyanto; Dwi Cahyo Kartiko (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2022)
Physical education is an important part of developing students' interests and talents in schools. Teachers must have a strategy for learners. This research aims to analyze the implementation of the inquiry learning method and group investigation on participation and critical thinking of students. This research was quasi-experiment by using two group pretest-posttest design. The sample in this research were 51 eighth grade students of SMPN 4 Pamekasan. The data collection was carried out using questionnaires and students’ activity assessment sheets. Furthermore, the data analysis was carried out univariate by using the SPSS application. The results of this study in group 1 with the inquiry learning method showed an average increase in student participation by 5%, and critical thinking by 8.8%. Furthermore, the group investigation method in group 2 showed an average increase in student participation by 7.3% and critical thinking by 15.2%.